PENATALAKSANAAN HOLISTIK PADA ANAK USIA 2 TAHUN DENGAN DIARE AKUT TANPA DEHIDRASI MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS KEDATON - Kirana, Falahdila Rebika; Angraini, Dian Isti (Medula, 2024)
Diarrhea is the second cause of death in children under five years in developing countries. Diarrhea indicates an infection in the digestive tract. Applying the principles of family medicine and implementing holistic management based on the patient-centered, family-focused, and community-oriented approach grounded in Evidence Based Medicine. This study is a case report utilizing primary data obtained through anamnesis, physical examination, and home visits to get family, psychosocial, and enviromental data. Secondary data were obtained from the patient’s medical records. A 2-years-old female patient came with watery stools from 2 days ago. Patient didn’t care about self-hygiene with washing her hands. Patient also often buy snack near her house which is not healthy. The patient was diagnosed with acute diarrhea without dehydration. Holistic management was performed with a family physician-designed approach for A 2-years-old female patient, with acute diarrhea without dehydration based on the initial holistic diagnosis. The intervention has improved the patient’s knowledge and changed some behaviours of the patient and her family.